3D Imaging of the Transparent Mycobacterium tuberculosis-Infected Lung Verifies the Localization of Innate Immune Cells With Granuloma - Kang, Gyeong-Yi; Rhyu, Hyeong-Jun; Choi, Hong-Hee; Shin, Sung Jae; Hyun, Young-Min (Frontiers in Cellular and Infection Microbiology, 2020)
Using a novel tissue-clearing method, we aimed to visualize the three-dimensional (3D) distribution of immune cells within Mycobacterium tuberculosis (Mtb)-infected mice lungs. Ethyl cinnamate-based tissue clearing of Mtb-infected mice lungs was performed to obtain transparent lung samples, which were then imaged using a light sheet fluorescence microscope. Using the 3D images, we performed quantitative analysis of the immune cell population within multiple granulomas. In addition, to compare the data from the tissue clearing method, we performed histopathological and immunofluorescence analyses, and flow cytometry. We then created 3D images of the Mtb-infected lung that successfully demonstrated the distribution of blood vessels, immune cells, and granulomas. Since the immune cells within a granuloma could be separately selected and counted, the immune cell population within a specific lesion could be quantified. In addition, macroscopic analysis, e.g. the size or shape of a granuloma, as well as microscopic analysis could be performed as intact lung samples were used. The use of the tissue clearing method in infected lungs could be a novel modality for understanding the role of the immune system in the pathogenesis of tuberculosis.